Sugar beet pulp as a carrier for Lactobacillus paracasei in lactic acid fermentation of agro-industrial waste - Mladenović Dragana; Đukić-Vuković Aleksandra; Radosavljević Miloš; Pejin Jelena; Kocić-Tanackov Sunčica; Mojović Ljiljana (Journal on Processing and Energy in Agriculture, 2017)
Lactic acid (LA) has gained considerable importance in the global market due to a wide range of applications. Because of the growing demand for food and feed, the use of lignocellulosic residues, by-products and waste streams is highly needed for commercial LA production. This study investigated the possibility of using potato stillage and sugar beet molasses for LA and biomass production by Lactobacillus paracasei NRRL B-4564 immobilized on sugar beet pulp. Adsorption of L. paracasei enabled easy separation of bacterial biomass from the fermentation media and its efficient reuse in three successive batch cycles. Total LA concentration of 146 g L-1 and average productivity of 1.03 g L-1 h-1 were achieved on waste substrate using bacterial cells immobilized on a natural carrier without mineral and nitrogen supplementation. The solid part of fermentation media remaining after LA fermentation is a valuable co-product, which could be used as animal feed rich in probiotic biomass.